A proposal to investigate the problems of three-phase distribution feeders supplying power to SWER systems - Hosseinzadeh, N.; Wolfs, Peter; Senini, S.; Seyoum, D.; Turner, J.; Loveday, A. (University of Queensland, 2004)
Long distribution feeders connected to Single Wire Earth Return (SWER) systems are unique sub-systems of the electric power network in Australia, especially in the State of Queensland. Since the SWER systems are connected between two phases of a distribution line via an isolating transformer, they are inherently unbalanced loads.In this paper a proposal will be developed to investigate the problems associated with the SWER systems and to suggest possible solutions. The study is based on an actual distribution feeder supplying power to several SWER lines in a rural area of the State of Queensland, Australia. Some issues will be addressed including suggestions for correcting the unbalanced operation, high energy losses, voltage and load profile, and the quality of power supplied to the customers.